Continuity study of spider diversity in Universiti Teknologi MARA (UiTM) Negeri Sembilan Branch, Kuala Pilah Campus, Negeri Sembilan, Malaysia / Nur Syafiqah Nazimah Azhari and Nursyazni Abdul Rahim - Azhari, Nur Syafiqah Nazimah; Abdul Rahim, Nursyazni (2022)
The data of the arachnids especially spider species in Malaysia are lacking due to the threats of the rainforest which is known to be the habitats of the species. Ninety-nine samples of spiders have been identified and documented in this study conducted in Universiti Teknologi MARA (UiTM) Negeri Sembilan Branch, Kuala Pilah Campus area with 11 families that consist of Araneidae, Corinnidae, Deinoppidae, Linyphiidae, Lycosidae, Oxyopidae, Pholcidae, Pisauridae, Salticidae, Sparassidae and Trachelidae. Sample collections were conducted at three different sites inside the campus using two different sampling techniques (active and passive). The highest abundance of spiders was in Site A (44%) but Lycosidae revealed to be the most abundant between the spider families. Site C had the uttermost diversity indices where Shannon-Wiener index, H' = 1.55, evenness index, E = 0.71 and richness index, RI = 8.70 due to 13 spider species spotted in the site. This study is in continuity with preliminary surveys done at Forest Reserve in UiTM Negeri Sembilan Branch, Kuala Pilah Campus with much longer sampling time period and it revealed that diversity increased to 23 genera collected from the whole campus area in present study as compared to 13 genera from previous study. The continuation of arachnid study is beneficial to the ecosystem to conserve the spider's species and habitats.